Exit options and the allocation of authority - Helmut Bester; Daniel Krähmer (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2013)
We analyze the optimal allocation of authority in an organization whose members have conflicting preferences. One party has decision-relevant private information, and the party who obtains authority decides in a self-interested way. As a novel element in the literature on decision rights, we consider exit option contracts: the party without decision rights is entitled to prematurely terminate the relation after the other party's choice. We show that under such a contract it is always optimal to assign authority to the informed and not to the uninformed party, irrespective of the parties' conflict of interest. Indeed, the first-best efficient solution can be obtained by such a contract.
Keywords: D23; D82; D86; 330; authority; decision rights; exit options; incomplete contracts; asymmetric information